Ze Wschowy do Strasburga przez Bazyleę – przypadki edukacyjne Jana Jakuba Doldego (1717–1789) - Tomczak, Robert T. (Biuletyn Historii Wychowania, 2024)
Johann Jacob Dolde (1717–1789) was a poor son of a barber from a small border town of Wschowa. From an early age, however, he longed to become a trained doctor of medicine. In order to achieve his goal, as an adolescent, he travelled abroad in order to receive proper education. His journey of several years took him through Poland, Royal Prussia, Ducal Prussia, Courland, Russia, Sweden, France, Switzerland, and finally ended in Alsace (Strasbourg), the land of his ancestors. Dolde described his memories of this journey in a short biography. The aim of this article, therefore, is to provide insight into the educational journey of Johann Jacob Dolde, and to show his determination during the numerous journeys. Indeed, he eventually fulfilled his dream and started a family in Strasbourg. His journey was part of the peregrination medica model and, as his memoirs are not known in Polish literature, is valuable historical material.